The effects of transcranial magnetic stimulation for freezing of gait in Parkinson’s disease: a systematic review and meta-analysis of randomized controlled trials - Liu, Zicai; Wen, Xin; Xie, Xiuying; Liu, Yangyou; Tan, Cheng; Kuang, Shuanghong; Liu, Huiyu (Frontiers in Aging Neuroscience, 2024)
Background: Freezing of gait (FOG) is one of the most disabling gait disturbances in Parkinson's disease (PD), affecting mobility and balance severely, thereby leading to an increased risk of falls.The purpose of this systematic review and meta-analysis was to investigate the effects of transcranial magnetic stimulation on FOG in PD.Methods: Based on PRISMA guidelines, we searched the databases of MEDLINE (PubMed), Cochrane Library, PEDro, Embase, and Web of Science. Studies of the English language published up to July 2023 were searched. We retrieved for studies of randomized controlled trials (RCTs) of transcranial magnetic stimulation to treat FOG after PD and screened by inclusion and exclusion criteria. Risk of bias was assessed using the Cochrane Collaboration's tool (Revman5.30).Characteristics of RCTs were extracted. The heterogeneity of the trials was measured by I² statistic.The effect size was expressed by a standardized mean difference (SMD) with a 95% confidence interval (CI).Results: A total of 488 articles were screened, after screening sixteen RCTs involved in 408 patients were included in the qualitative analysis, and 15 RCTs were included in meta-analysis. The outcome measures included FOG-Q, walking time, TUG, and UPDRS. Six studies used FOG-Q as outcome measure, six studies used walking time, four studies used TUG, and six studies used UPDRS.Compared with placebo treatment, transcranial magnetic stimulation has positive significant effects in improving gait status with increased walking speed (SMD = -0.41, 95% CI =-0.75 to -0.06, I 2 = 7% P = 0.02), FOG-Q scores (SMD = -0.55, 95% CI =-0.89 to -0.21, I 2 = 29%, P = 0.002, UPDRS scores (SMD = -1.08, 95% CI =-1.39 to -0.78, I 2 = 49%, P ＜0.001) and the time of TUG (SMD = -0.56, 95% CI =-0.88 to -0.23, I 2 = 25%, P = 0.02) decreased.Transcranial magnetic stimulation could significantly improving gait conditions in PD patients with FOG.